Desenvolvimento de superfícies seletivas para coletores solares com deposição multicamadas de Cr e SiO2 - Silva Neto, José Felix da (2017)
Solar thermal conversion consists in the use of the heat transmitted by solar radiation to heat up water in residences and to produce steam for industrial processes. It is one of the simplest ways of harnessing energy from solar radiation. Despite this, there are limitations in its use mainly related to processes that require higher temperatures. Selective surfaces are a recent and effective alternative in the quest for increased thermo solar conversion efficiency. This work proposes to develop a new type of selective Cermet surface, composed of two (100nm and 50nm thick, volumetric fractions of 0,40 and 0,15 in Cr, respectively) or three sublayers (the same previous configuration with a Layer of SiO2 with a thickness of 20 nm), covering two types of metal substrates: copper and 304 stainless steel. These coatings were prepared by co-sputtering and optically characterized in the ultraviolet, visible, near infrared and mid-infrared bands of the electromagnetic spectrum. Morphological evaluation of the coatings by atomic force microscopy (AFM) and optical profilometry, besides the chemical characterization by X-ray diffraction, were performed. Results showed that the films produced presented high optical selectivities, especially the films deposited on 304 stainless steel substrate. It was also observed that the Cr was integrated to the SiO2 chain, due to the presence of Cr-O-Si links in its structure. In addition, the structure of the formed films presented amorphous character in the two configurations evaluated. It was also shown that the inclusion of an anti-reflective coating for infrared radiation had the expected effect and caused a reduction in the emissivity of the coatings evaluated, besides having a reducing effect on the surface roughness of the coatings.